Kualitas Perairan Sungai Anyar (Anak Sungai Bengawan Solo) Surakarta Ditinjau Dengan Indeks Keanekaragaman Fitoplankton - Setyowati, Nur Aini Dewi; , Efri Roziaty, S. Si., M. Si (2017)
Activities around the Anyar River such as ongoing development projects, domestic waste, livestock, and fishing can affect changes in physical, chemical and biological conditions so as to affect water quality and biota survival in it. The purpose of this research is to know the water quality in Anyar River Surakarta based on phytoplankton diversity index. This research is a quantitative explorative research. The method used is purposive sampling by setting 3 stations that are Station A on the upstream with activities project development and domestic waste, Station B to the center of with activities domestic waste and fishing , and Station C on the downstream with activities development projects and livestock and research is conducted twice repetition. Phytoplankton identified 52 species of 39 genera and 6 main divisions of Chyanophyta (4 genera, 6 species), Bacillariophyta (17 genera, 27 species), Chrysophyta (3 genera, 4 species), Euglenophyta (2 genera, 2 species) Dinophyta (1 genus, 1 species), and Chlorophyta (10 genera 12 species). The diversity index (H ') ranges from -1.94 to -2.60 means the quality of the unstable biota and the quality of the polluted waters is heavy.